Spectroscopic characterization of rare events in colloidal particle stochastic thermodynamics - Otani, Sandro K.; Martins, Thalyta T.; Muniz, Sérgio R.; de Sousa Filho, Paulo C.; Sigoli, Fernando A.; Nome, René A. (Frontiers in Chemistry, 2022)
Given the remarkable developments in synthetic control over chemical and physical properties of colloidal particles, it is interesting to see how stochastic thermodynamics studies may be performed with new, surrogate, or hybrid model systems. In the present work, we apply stochastic dynamics and nonlinear optical light-matter interaction simulations to study nonequilibrium trajectories of individual Yb (III):Er (III) colloidal particles driven by two-dimensional dynamic optical traps. In addition, we characterize the role of fluctuations at the single-particle level by analyzing position trajectories and time-dependent upconversion emission intensities. By integrating these two complementary perspectives, we show how the methods developed here can be used to characterize rare events.